The geology of Kudat Peninsula, Sabah: New insights from field geology and subsurface interpretation - Zainuddin, N.M. (Geological Society of Malaysia, 2019)
Northern Borneo is a geologically complex region influenced by the rifting and opening of the South China Sea during Oligocene to Middle Miocene. Kudat Peninsula, which lies in the northern tip of north Borneo expose part of this complex geology. Detail geological study of an area with a comprehensive and thorough understanding of the tectonic history avails in conceiving the geological evolution. Geological and geophysical study was conducted in Kudat Peninsula and offshore of the Kudat Peninsula to evaluate the structural framework and tectonic history of the peninsula. Four formations underlying Kudat Peninsula are Ophiolite Basement, which is overlain by younger deposits, Crocker Formation, Kudat Formation and a chaotic deposit known as mélange. Kudat Peninsula is underlain mainly by the Kudat Formation which comprises three members, Tajau Member, Sikuati Member and Gomantong Member, made up of interbedded sandstone and mudstone. Kudat Formation is believed to be sitting on top of the basement rock or ophiolite rock. We propose that the Kudat Formation and the basement layer extended into the offshore region of NW Sabah and the mélange unit found in the north of the peninsula is originated from the older formations such as the Kudat Formation and the ophiolitic basement that had been faulted, deformed and uplifted to the surface through faulting. © 2019 Geological Society of Malaysia. All rights reserved.